Peningkatan Kemampuan Literasi Membaca Santri Pondok Pesantren Ar Ridwan Rōmly Al-Maliky Melalui Model Pembelajaran Inquiry-Based Learning Pada Pelajaran Bahasa Indonesia - Abdul Basith; Ainu Zuhriyah (Journal on Education, 2025)
This study aims to improve the reading literacy skills of students at the Ar Ridwan Rōmly Al-Maliky Islamic Boarding School through the application of the Inquiry-Based Learning (IBL) model in Indonesian language lessons. The low ability of students to understand reading content, analyze text structure, and draw conclusions indicates the need for the development of a more active and challenging learning model. This research is a Classroom Action Research (CAR) using the Kemmis and McTaggart approach, consisting of two cycles. The research subjects included 32 high school level students who took Indonesian language lessons. The research instruments consisted of reading literacy tests, observation sheets, and student response questionnaires. The results showed an increase in the average reading literacy score of students from 62 in the pre-cycle to 74 in cycle I and 86 in cycle II. The students' activities in asking questions, discussing, and analyzing texts also showed a significant increase. These findings show that the IBL model is effective when applied in Indonesian language learning in Islamic boarding schools to improve students' reading literacy skills in terms of both cognitive aspects and learning attitudes.